MIRAGE syndrome: a case report of de novo SAMD9 c.884del p.(Pro295GlnfsTer104) variant and a novel phenotype of pyloric stenosis - Mohamad M. Assker; Mahdia Al Haidar; Marwan Faris; Ahmed Emara; Yousef Al Abrach; Maryam Al Shehhi (Egyptian Journal of Medical Human Genetics)
Abstract Background MIRAGE syndrome is a rare multisystem disorder characterized by myelodysplasia, infection, growth restriction, adrenal hypoplasia, genital phenotypes, and enteropathy, resulting from mutations in the SAMD9 gene. This syndrome is notably rare, with fewer than 60 documented cases globally. We present a unique case of an 8-month-old boy with MIRAGE syndrome exhibiting a previously unreported clinical manifestation of pyloric stenosis, contributing to the expanding phenotypic spectrum of the disorder. Case presentation An 8-month-old boy who was born full-term with a birth weight of 3.8 kg presented with multiple infections, including urinary tract infection, pneumonia, and viral illnesses, requiring hospital admissions. At three months, he was diagnosed with pyloric stenosis following recurrent vomiting. Further complications included respiratory failure, developmental delay, and failure to thrive. Genetic testing identified a heterozygous SAMD9 mutation (c.884del, p.(Pro295GlnfsTer104)) and an X-linked pathogenic duplication affecting 21 genes. These findings confirmed the diagnosis of MIRAGE syndrome. Conclusions This case underscores the phenotypic diversity of MIRAGE syndrome, highlighting pyloric stenosis as a novel clinical feature. Early recognition and a comprehensive, multidisciplinary approach are crucial for managing the syndrome's severe and varied manifestations. More research needs to be undertaken to further understand the genotypes of MIRAGE syndrome and its phenotypical manifestations.